Effects of Fusarium Proliferatum infection on the quality and respiratory metabolism of postharvest asparagus. Issue 2 (3rd July 2022) - Zhang, Xiaoyun; Yan, Xueli; Hu, Wanying; Dhanasekaran, Solairaj; Legrand Ngolong Ngea, Guillaume; Godana, Esa Abiso; Gu, Xiangyu; Zhao, Lina; Zhang, Hongyin
ABSTRACT: Sugars and organic acids are important factors associated with the postharvest quality of fruits and vegetables, but respiratory metabolism effects the metabolite contents. The objectives of this study were to explore the affects of Fusarium proliferatum infection on the postharvest quality and respiratory metabolism of green asparagus. It was found that F. proliferatum caused the soluble sugar concentration of asparagus to increase over the first 2 d of storage and then decrease again to become significantly lower than the control at 4 d. The titratable acidity (TA) of infected asparagus also increased from day 2 to day 6 and then decreased to become significantly lower than the control. Similarly, the key enzyme activities of the Embden-Meyerhof-Parnas (EMP) pathway, tricarboxylic acid (TCA) cycle, and pentose phosphate pathway (PPP) increased in pathogen-infected asparagus at the beginning of storage and then decreased to become lower than the control at the end. These findings demonstrate that F. proliferatum caused quality deterioration and an impairment of respiratory metabolism in postharvest asparagus. This research helps to clarify the relationships between pathogen infection, physiological metabolism, and asparagus quality and will provide valuable information for the control of postharvest diseases of asparagus.